2020
DOI: 10.1055/a-1328-5126
|View full text |Cite
|
Sign up to set email alerts
|

Risk of colonoscopy-related complications in a fecal immunochemical test-based population colorectal cancer screening program

Abstract: Background and study aims: The likelihood of advanced or synchronous neoplasms is significantly higher in fecal immunochemical test (FIT)-positive subjects than in the general population. The magnitude of colonoscopy-related complication rate in FIT-positive subjects, however, remains unknown. This study aims to elucidate the colonoscopy-related complication rate after positive FIT and compared with colonoscopy performed for other purposes. Patients and methods: Information regarding colonoscopy after positiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…Hsu et al (44) used National Health Insurance Research Database codes for stringent and broad definitions of colonoscopy-related complications. All cases who had an episode of admission within 30 days after colonoscopy were assessed to determine colonoscopy-related adverse events in another study (43).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hsu et al (44) used National Health Insurance Research Database codes for stringent and broad definitions of colonoscopy-related complications. All cases who had an episode of admission within 30 days after colonoscopy were assessed to determine colonoscopy-related adverse events in another study (43).…”
Section: Resultsmentioning
confidence: 99%
“…A total of 13,592,454 patients across 31 studies underwent CRC screening using either gFOBT or FIT. Seventeen studies (3,(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41) reported on outcomes in patients using gFOBT and 14 studies (39,(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55) reported on FIT. Overall, 771,730 colonoscopies were performed in patients with an abnormal FIT (571,971) or positive gFOBT (199,759).…”
Section: Resultsmentioning
confidence: 99%
“…In conclusion, patients receiving antithrombotic treatment are at increased risk of a positive FIT and at a marginally decreased risk of CRC or high risk adenoma detection at subsequent colonoscopy. Treatment with NOACs is increasing and the fact that it leads to a more than twofold increase in FIT positive results could highlight the need for other adjunctive testing (using novel blood-or stool-based biomarkers), both to decrease the number of colonoscopy-related complications and to lessen the burden on colonoscopy units [33,34]. Future studies should address this issue when these biomarkers are being employed in clinical practice.…”
Section: Crc In Fit-positive Individuals Undergoing Colonoscopymentioning
confidence: 99%
“…Key quality indicators for colonoscopy include adequate bowel preparation, cecal intubation rate, withdrawal time, and adenoma detection rate. By assessing and monitoring key quality indicators, medical professionals can identify areas for improvement, implement necessary changes, and ensure that patients receive the highest standard of care during colonoscopy procedures 7,8 …”
mentioning
confidence: 99%
“…By assessing and monitoring key quality indicators, medical professionals can identify areas for improvement, implement necessary changes, and ensure that patients receive the highest standard of care during colonoscopy procedures. 7,8 High-quality bowel preparation plays a crucial role in ensuring optimal outcomes during colonoscopy procedures. Inadequate bowel preparation is associated with lower rates of detecting neoplastic polyps, higher rates of incomplete procedures, and the need for more frequent repeat procedures.…”
mentioning
confidence: 99%